2021
DOI: 10.1016/j.cellimm.2021.104398
|View full text |Cite
|
Sign up to set email alerts
|

An outlook on antigen-specific adoptive immunotherapy for viral infections with a focus on COVID-19

Abstract: Graphical abstract Adoptive immunotherapy options currently under trial for COVID-19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 95 publications
0
23
0
Order By: Relevance
“… 20 , 21 To isolate functional Ag-specific T cells from PBMC, magnetic-activated peptide-MHC multimer-guided enrichment and magnetic-activated cytokine capture-based sorting have been used as the two methods for reliably reproducible GMP-grade production. 2 , 3 , 13 , 15 Using the latter method, WT1-reactive T cells were enriched and isolated from two groups of healthy donors and patients with Wilms tumor in this study. It was revealed that greater frequencies of these cells can be enriched from patients with Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 , 21 To isolate functional Ag-specific T cells from PBMC, magnetic-activated peptide-MHC multimer-guided enrichment and magnetic-activated cytokine capture-based sorting have been used as the two methods for reliably reproducible GMP-grade production. 2 , 3 , 13 , 15 Using the latter method, WT1-reactive T cells were enriched and isolated from two groups of healthy donors and patients with Wilms tumor in this study. It was revealed that greater frequencies of these cells can be enriched from patients with Wilms tumor.…”
Section: Discussionmentioning
confidence: 99%
“…T cells reactive against specific antigens (Ags) have emerged as potent targeted immunotherapies for certain cancers and hard-to-treat viral diseases. 1 , 2 Although the immune system harbors different clones of Ag-reactive T cells to endogenously eliminate cancerous or virally infected cells, 3 the body may be caught in a losing battle because of the small number of these cells. Hence, to augment Ag-specific T cell responses in vivo , large-scale in vitro (or ex vivo ) enrichment and expansion of the relevant T cell lines may be a solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Baricitinib, a JAK1/2-selective kinase inhibitor, is used in rheumatoid arthritis treatment and severe cases of COVID-19, preventing progression to ARDS (Ai et al 2022 ). Four anti-SARS-CoV-2 monoclonal antibody products have received EUA from US-FDA for non-hospitalized patients, including sotrovimab, bamlanivimab, etesevimab, and “imdevimab and casirivimab” (REGEN-COV) ( https://www.covid19treatmentguidelines.nih.gov/therapies/anti-sars-cov-2-antibody-products/anti-sars-cov-2-monoclonal-antibodies/ ; Monzavi et al 2021 ). Thus, developing such novel immunotherapies can target viral infection and improve the clinical outcomes.…”
Section: Covid-19 Therapeutic Approachesmentioning
confidence: 99%
“…Immunotherapy is defined as utilizing and manipulating the host's immune system to eliminate the affliction. Cell therapies using autologous or allogeneic immune cells have shown potential as a therapeutic approach in solid and hematological malignancies [20] , chronic viral infections ( e.g. HIV) [21] , and refractory viral infections in hematopoietic stem cell transplantation (HSCT) patients [22] , [23] .…”
Section: Immune Cell-based Therapies Against Sars-cov-2 Infectionmentioning
confidence: 99%